Characteristic Features of The Parameters of The Heart in Patients with Combined Mitral Malformations - Kutlikova G. M. (Scholars Digest Publishing, 2023)
Using ultrasound examination with age-related features significantly expands the possibility of studying intimate mechanisms of functioning of the heart in normal and pathological cases. it would allow to establish many age-related patterns of disorders not only during systole, but also in diastole in various diseases of the cardiovascular system, indicate the initial signs of development of cardiac failure, objective estimating the role of several compensatory mechanisms, influencing different functional tests, which has invaluable importance for practical medicine.
Keywords: Age-related features of cardiac echoparameters, combined mitral defect, diameter of aortal ring.